Leadership and Next Generation Unmanned System Integration - Clemens, Amy T; Huffman, Leslie (Journal of Accounting, Business and Management (JABM), 2024)
The purpose of this study is to explore the challenges and successes Aerospace Industry leaders encounter regarding the safe integration of unmanned aerial vehicles (UAVs) that weigh over 55 lbs. into the National Airspace System (NAS). Specifically, how will leadership in the Aerospace Industry respond to a rogue UAV flying in the National Airspace when the communication link is lost due to hardware or software failure. A qualitative intrinsic case study was used for this study. Using snowball sampling, a total of 15 participants responded to 12 open-ended survey questions. The findings presented challenges the Aerospace Industry must overcome for larger UAVs to fly in the national airspace. The major themes identified were: (a) Issues with integration efforts between the FAA and the Aerospace Industry, (b) Safety in the national airspace for all aircraft, and (c) Progress and Challenges. The study recommends that the Aerospace Industry consider implementing Industry 4.0 technology into their business, examining the UAV flight management system, and a redesigning of the COA process.